Symposium on the present and future of inland transport - Carter, C. F.; Bailie, J. C.; Streight, R. L.; Johnson, Martin; Black, W. (Statistical and Social Inquiry Society of Ireland, 1957)
The Statistical Society of Ireland is nearly 110 years old, and it has discussed the problems of Irish transport on some twenty-five occasions: for instance, over 90 years ago it was discussing the nationalisation of the railways. But transport problems on road and rail have never been so urgent, complex and interesting as they are today.
Read before the Society, 14 December 1956
Keywords: Railway transport; Great Northern Railway Board; Northern Ireland transport; Road transport; 314.15